DESIGN OF DECISION SUPPORT SYSTEM APPLICATION FOR EMPLOYEE PERFORMANCE ASSESSMENT USING WEIGHTED SUM MODEL (WSM) METHOD IN PT VELOXA VIGGO INTI TEKNOLOGI - Ach Nofal Kurniawan; Agus Dwi Churniawan; Nunuk Wahyuningtyas (Jurnal Sistem Informasi Universitas Dinamika, 2021)
PT. Veloxa Viggo Inti Teknologi is a telecommunication service company which requires employees who have extensive skills and insight so that in the future they can make the company grow rapidly. Employees who have broad skills and insight can influence the profits that the company gets. Therefore, managers need a decision-making system that can assist companies in assessing employees with company work standards